Early Islamic Art and Architecture - Ewert, Christian (Journal of Semitic studies, 2004)
Early Islamic Art and Architecture Jonathan M.Bloom (ed.), (The Formation of the Classical Islamic World 23). Ashgate, Aldershot 2002. 420 + 131 b & w illustrations. Price: £75.00 . ISBN: 0-86078-705-2